Interracial communication and perceptions of the compatibility of different races among Malay and non-Malay students in a public university in Malaysia - Tamam, Ezhar; Idris, Fazilah; Yee, Wendy Mei Tien (Elsevier, 2011)
Drawing on contact theory and the theory of cognitive development, educators and policy makers have encouraged students of different races to intermingle. However, the benefits of such contact in a Malaysian multiracial public university in which there is no real racial majority have not been adequately assessed. This study examined the extent to which interracial communication with peers contributes towards students' perceptions of the compatibility of different races. A total of 377 students participated in this self-administered survey. The results of the stepwise regression analyses showed that the quality of the students' interracial communication with their peers (not the intensity of the interracial communication) was a significant predictor of their perceptions of the compatibility of different races. This applied to both the Malay and the non-Malay students. The theoretical and practical implications of the findings were discussed.